Modification of magnetic properties of epitaxial Co/Cu multilayers by 1 MeV C+ irradiation - Sung, MC; You, DG; Park, HS; Lee, JC; Ie, SY; Kim, IS; Lee, J; Whang, CN; Im, S; Jeong, K; Kim, TG; Yang, JS; et al. (AMER INST PHYSICS, 2001)
Epitaxial [Co/Cu](10) grown on Si (001) has been irradiated by 1 MeV C+ with a dose of 1x10(16)/cm(2). The intrinsic characteristics of epitaxy, such as crystal structure and fourfold magnetic anisotropy, are conserved after ion irradiation. However, the extrinsic magnetic properties are changed such that the coercivity decreases and the squareness of the hysteresis loop is noticeably improved. The intensity of the Cu (200) peak in the x-ray diffraction pattern increases about three times and its half-width decreases after irradiation. It is concluded that the changes of magnetic properties induced by ion irradiation result from the grain growth and the improved crystalline quality. (C) 2001 American Institute of Physics.
Keywords: ION-BEAM MODIFICATION; FERROMAGNETIC-RESONANCE; MEDIA; CO